DRUG USE RECOMMENDATIONS FOR COLISTIN INJECTION IN THE ADULT POPULATION - Amir, Muhammad; Dodani, , Sunil; Nasim, Asma; Babar, Zaheer Udin (Journal of Ayub Medical College Abbottabad, 2023)
Background: Colistin, also known as Polymyxin E, was the first polymyxin antibiotic. This bactericidal antibiotic plays a vital role as salvage therapy for untreatable gram-negative. Colistin dosing regimens differ worldwide. The published guidelines have different recommendations on the dosing regimens. Further confusion exists due to two different dosing units. Currently, Pakistan has no national guidelines for colistin use. The guideline was developed with the aim of improving the safety profile by developing standardization in colistin use and thus reducing the confusion amongst clinicians. Method: The guideline was developed by a panel of five actively practising infectious disease specialists (physicians and pharmacists) with clinical and research expertise in this particular field. Different literature and international guidelines along with institutional data were used to develop the guideline. Conclusion: The guideline provides ten recommendations on prescribing, transcribing, posology, preparation, administration and monitoring of colistin use. The guideline will give Pakistani healthcare providers a standard approach to using rationally and effectively, and to clear confusion and questions about this medicine.